Dye Sensitized Solar Cells Based on Hydrazonoyl Synthetic Dyes - Monzir S. Abdel-Latif; Amal Batniji; Taher M. El-Agez; Malak J. Younis; Hatem Ghamri; Bassam A. Abu Thaher; Basem S. Qeshta; Fakhr M. Abu-Awwad; Sofyan A. Taya (Журнал нано- та електронної фізики)
A group of chemical sensitizers of two hydrazonoyl based derivatives were synthesized. These derivatives contain a good  system for efficient light absorption and oxide sensitization. Precursor structure I was reacted with 2,6-diaminopyridine, 2-aminobenzoic acid, 4-aminobenzoic acid, 2-aminopyridine, 2,6-dinitrophenylhydrazine, and diphenylamine. The other precursor, structure (II), was reacted with 2-aminobenzoic acid, 2-amino-3-methyl, and 2-amino-4-methylpyridine. A total of 9 dyes were prepared and evaluated as sensitizers for dye-sensitized solar cells (DSSCs). Full computational calculations using DFT B3LYP 6-31+G were carried out for evaluation of band edge and band gap energies of all compounds. The absorption spectra of these dyes as well as cyclic voltammetry were used for the measurement of the HOMO, LUMO, and energy band gaps. The photovoltaic performance of the fabricated DSSCs was measured in different solutions comprising water, alcohol, phenylhydrazine, and dinitrophenylhydazine.